Features of registered occupational diseases in Greece: a veil of ignorance / Andamento delle malattie professionali in Grecia: il velo dell’ignoranza - Rachiotis, G.; Alexopoulos, C.G.; Symvoulakis, et al., E.K. (La Medicina del Lavoro, 2012)
Introduction: Background: Under-registration of occupational diseases is a global problem. Objectives: The aim of this study was to describe the characteristics of the reported cases of occupational diseases, in the context of the largest insurance scheme in Greece. Methods: Socio-demographic characteristics related to the identified cases of occupational diseases were collected from the archives of the special medical committee of the Social Insurance Institute (Idrima Koininikon Asfaliseon, IKA) for the year 1999. This year was chosen given that it largely represents the highest number of registered occupational diseases in comparison to the period 2000-2009. Results: Sixty-seven (67) occupational diseases were recognized (3.4 cases/100,000 employees). There were 32 new cases (incidence rate: 1.64/100,000 employees). Occupational skin conditions and diseases of the respiratory system accounted for 85% of all diagnoses. Builders and unskilled blue collar workers were the most frequent occupational groups affected. Conclusions: These findings indicate a high rate of under-registration of occupational diseases in Greece, compared to data from the European Union. This under-registration could be attributed to a variety of limitations related to the current model of occupational health in Greece. The present pattern of registered occupational morbidity reflects the under-development of occupational health in Greece and stresses the need for further and intensified work in order to create modern occupational health services in this country.Andamento delle malattie professionali in Grecia: il velo dell’ignoranzaIntroduzione: È un fatto di preoccupazione in tutto il mondo la sottostima delle malattie professionali, data anche la scarsa propensione alla loro denuncia. Obiettivi: Analizzare le caratteristiche dei casi registrati di malattie occupazionali da parte del più grande gruppo assicurativo in Grecia. Metodi: Dagli archivi dell’anno 1999 dell’apposito Comitato Medico dell’Istituto di Assicurazione Sociale (Idrima Koininikon Asfaliseon, IKA) sono state ricavate le caratteristiche socio-demografiche dei casi riconosciuti affetti da malattie occupazionali. L’anno 1999 è stato scelto perché esso ha visto di gran lunga il maggior numero di malattie occupazionali registrate in confronto all’arco temporale 2000-2009. Risultati: Sono stati riconosciuti sessantasette (67) casi di malattie occupazionali (3.4 casi ogni 100.000 occupati) ed i nuovi casi sono stati 32 (1.64 ogni 100.000 occupati). Le affezioni cutanee e le malattie dell’apparato respiratorio hanno rappresentato l’85% di tutte le diagnosi. Gli addetti all’industria delle costruzioni e gli operai non specializzati rappresentano i gruppi più frequentemente colpiti. Conclusioni: Questi risultati indicano come vi sia un considerevole numero di malattie occupazionali non denunciate in Grecia in confronto a quanto avviene nell’Unione Europea. Le motivazioni di questa scarsa denuncia devono essere attribuite ad una serie di limitazioni legate all’attuale modello di salute occupazionale in Grecia che di fatto è da considerare molto lontano da quanto è seguito nei paesi industrializzati e mette in evidenza la necessità di creare servizi maggiormente adeguati di Medicina del Lavoro in Grecia.